A national registry-based study of surgery and demography comparing internationally adopted and children born in Sweden with cleft lip and/or palate. Issue 1 (28th February 2023) - Schölin, Johnna Sahlsten; Rizell, Sara; Paganini, Anna; Mark, Hans
Abstract: This national registry-based study compares surgical procedures, demography, and concurrent medical conditions, in internationally adopted and Swedish-born children with cleft lip and/or palate until the age of five years. Data on the cleft type and gender for 331 internationally adopted children and 2064 Swedish-born children born from 2007 to 2018, were extracted from the registry and analyzed. Data on surgical procedures performed in Sweden and concurrent medical conditions and were collected for internationally adopted children and Swedish-born children with unilateral or bilateral cleft, born 2007–2013. A higher prevalence of unilateral and bilateral clefts ( p < 0.0001), as well as a predominance of male patients with unilateral clefts ( p = 0.0025), were identified among the internationally adopted children compared with children born in Sweden. Differences in the concurrence of other medical conditions in internationally adopted children versus Swedish-born infants were non-significant. Primary palatal surgeries performed in Sweden were significantly delayed for the adopted group. More secondary palatal surgeries such as speech improving surgery and palatal re-repair were needed for internationally adopted children ( p < 0.0001) until age five. Conclusions : The Swedish CLP Registry provided national coverage of the CL/P cohort. Internationally adopted children exhibited a predominance of more severe cleft types, a predominance of males, delayed primary palatal surgery and increased need for secondary surgeries before age five.